Women's Participation in Training on The Processing of Economic Value Rubber Seeds and Local Wisdom Based in Curahtakir Village, Jember - NurSekti, Marita; Sepiarti, Serafin Wisni (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
Curahtakir Village, located in Jember, is affiliated with PTPN XII and serves as a prominent rubber-producing community. A significant proportion of the village's population comprises women who are actively engaged in rubber-related labor. A significant quantity of rubber seeds is discarded and commercially traded at a price range of IDR 2000-3000 per kilogram. The absence of sufficient knowledge regarding the local potential necessitates the provision of training programs focused on the conversion of rubber seeds into high-value food products. The rubber seed chip products have the potential to enhance the local wisdom of Curahtakir Village. This research explains women's participation, empowerment through training for women, and training based on local wisdom. The study involved conducting interviews with female rubber workers, trainees, and members of the local community. The village chiefs serve as supplementary sources of information to obtain insights on the involvement of women in training programs. The findings indicated a significant level of active participation among women. During the pre-planning, the activities aimed at promoting women's participation persist in their planning and evaluation, despite encountering various obstacles, such as the challenges posed by their existing work commitments. The implementation continued to run well, the participants continued to follow the activity process to completion.